Framing Analysis of Online Media Coverage Regarding Environmental Issues: A Study of National News Portals in Indonesia - Aisa Setiawati; Ibrahim Sumantri (Journal of Creative Power and Ambition (JCPA), 2026)
The increasing participation of women in home industries has highlighted the importance of achieving a sustainable balance between work responsibilities and family life. Flexible working arrangements are widely regarded as a means of improving employees' well-being; however, their effectiveness in home-based employment remains inconsistent due to overlapping domestic and occupational roles. This study aims to systematically review the existing literature on the relationship between work-life balance and time flexibility among female employees in the home industry. The research employed a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. Relevant articles published between 2020 and 2026 were identified from reputable academic databases, screened based on predetermined inclusion and exclusion criteria, and analyzed using thematic synthesis. The review reveals that time flexibility generally enhances work-life balance by increasing schedule autonomy, job satisfaction, productivity, and psychological well-being. Nevertheless, flexible working arrangements do not automatically eliminate work-family conflict because women continue to face unequal domestic responsibilities, economic insecurity, blurred work-life boundaries, and continuous digital connectivity. The findings further indicate that family support, gender equality, organizational commitment, social protection, and digital competence are critical factors influencing the successful implementation of flexible work practices. This review contributes to the existing literature by providing an integrated understanding of the determinants and challenges of work-life balance among female home-industry workers while identifying research gaps and practical implications for policymakers, employers, and researchers. Developing gender-responsive employment policies and comprehensive support systems is essential for promoting sustainable work-life balance and strengthening the long-term competitiveness of home industries.